The Anxiety of Pregnant Women as a Determinant of Integrated Antenatal Care Visits During the Covid-19 Pandemic - Catur Prasastia Lukita Dewi; Indah Lestari; Noer Saudah (Kirana Publisher (KNPub), 2023)
Introduction: During this covid-19 pandemic, there are many restrictions on all routine services, including Maternal and Neonatal Health services, taking into account the prevention of transmission to pregnant women and health workers who examine them. In this situation, many pregnant women are reluctant to visit the Puskesmas or other healthcare facilities because of the mother's anxiety about being infected, especially with the new variant of covid-19. The purpose of the study was to describe the anxiety of pregnant women as a determinant of Antenatal Care (ANC) visits during the covid-19 pandemic. Methods: This research design is a descriptive correlational survey using a quantitative approach with a cross-sectional study design. Samples were taken with a total sampling of 230 respondents. The source of the data is the result of filling out the questionnaire sheet for the respondents. The questionnaire contains the identification of characteristics and an anxiety questionnaire using the Perinatal Anxiety Screening Scale (PASS). Results: ANC visits at the independent practice of obstetricians 42% and asymptomatic anxiety 75%. Health workers are expected to provide nursing services to be more intensive in providing health education and actual information about COVID-19 to pregnant women to reduce the risk of pregnancy complications due to anxiety.